Enhancing Effects on Vacuole-Targeting Fungicidal Activity of Amphotericin B - Ogita, Akira; Fujita, Ken-ichi; Tanaka, Toshio (Frontiers in Microbiology, 2012)
Invasive fungal infections are major threats for immunocompromised patients as well as for those undergoing cancer chemotherapy. Amphotericin B (AmB), a classical antifungal drug with a polyene macrolide structure, is widely used for the control of serious fungal infections. However, the clinical use of this antifungal drug is limited by its side effects and the emergence of drug-resistant strains. AmB lethality has been generally attributed to alterations in plasma membrane ion permeability due to its specific binding to plasma membrane ergosterol. Recent studies with Saccharomyces cerevisiae and Candida albicans reveal the vacuole disruptive action as another cause of AmB lethality on the basis of marked amplification of its activity in combination with allicin, an allyl-sulfur compound from garlic. The enhancing effect of allicin is dependent on the inhibition of ergosterol-trafficking from the plasma membrane to the vacuole membrane, which is considered to be a cellular response to protect against disintegration of the vacuole membrane. The polyol macrolide niphimycin (NM) also possesses vacuole-targeting fungicidal activity, which is greater than that of AmB and nystatin. The alkyl side chain attached to the macrolide ring of NM is considered to possess an allicin-like inhibitory effect on the intracellular trafficking of ergosterol. The vacuole-targeting fungicidal activity was additionally detected with a bactericidal cyclic peptide polymyxin B (PMB), and was markedly enhanced when administered together with allicin, monensin, or salinomycin. The synergistic fungicidal activities of AmB and allicin may have significant implications for the development of vacuole-targeting chemotherapy against fungal infections.